Character Education through RADEC Learning for V Grade Elementary School Students on Water Pollution Material - Arie Johana; Andi Suhandi; Babang Robandi (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
Character education is one of the most important parts of national education wher moral values are highly emphasized to students. This research aims to see the application of student character education through RADEC learning on water pollution material. This research use descriptive qualitative research methods. The subjects of this study consisted of 21 V grade students in on of the public elementary schools in sumedang district, cimalaka regency. Data collection was carried out after the research activity took place through the distribution of questionnaire to students. Processing the results of research data is determined based on the aspect of character education that appears through the percentage value of students answers then calculates the average results, and the research data is analysis qualitatively. The results showed that the use of the RADEC learning could show aspects of character education for V grade elementary school students about water pollution.